Safety Reporting for Auxiliary Medicinal Products in the Sibeprenlimab Phase-III Study According to the New European Union (536/2014) CT Regulation - Kumar, Retesh; Giri, Pratyush; Huang, Mai; Parikh, Nipa; Khare, Vikalp; Sheppard, Catherine; George, Vinu (Current Drug Safety, 2025)
<span class=
Keywords: auxiliary medicinal products